P152 Epidemiology and practice patterns in the management of lupus nephritis in Australia. (23rd March 2020) - Phoon, Richard; Brown, Fiona; Coates, Toby; Ford, Sharon; Irish, Ashley; Isbel, Nicole; Thomas, Mark; Wyburn, Kate
Abstract : Background: In Australia, Lupus Nephritis (LN) affects a culturally diverse population of patients. We established the Lupus Nephritis Australian Registry (LUNAR) to better understand the population of patients receiving Myfortic and other immunosuppressants, and to analyse the safety and efficacy of the treatments they received. Methods: A non-interventional, multicentre, registry of patients with biopsy-proven ISN/RPS class III, IV or V LN, treated with Myfortic or other immunosuppressants, was established. We collected baseline demographic and 6-monthly follow-up data over a 5-year period (2013–2018), including clinical data, laboratory tests and safety outcomes. Results: 149 patients were enrolled in LUNAR across 8 sites, with 83.7% female and a mean age of 38.8 years. Most patients were Caucasian (45.2%) – patients of Asian ethnicity (29.6%) and Aboriginal/Torres Strait Islander or Maori/Pacific Islander descent (10.4%) were significantly over-represented compared to the general population. The mean and median duration of SLE was 8.6 and 6 years, respectively (range 0–42 years), and of LN was 5.4 and 3.9 years, respectively (range 0–30 years). Most patients had class IV LN on their initial kidney biopsy (59.3%), with 21.5% having class III and 11.1% having class V LN. Immunosuppressants used prior to screening included corticosteroids (68.9%), mycophenolate mofetil ((MMF) 61.5%), Myfortic (41.5%) and cyclophosphamide (32.6%). At enrolment or during the study, most patients were treated with Myfortic (76.3%), MMF (65.2%) and/or hydroxychloroquine (67.4%). Rituximab and azathioprine were each started in 8.9% of patients during the study period. Kidney function was stable/improved for most patients over the study period and mycophenolate-based therapy was well-tolerated. Conclusions: LUNAR is the first study outlining the demographics, outcomes and practice patterns in the management of patients with LN in Australia. Acknowledgements: Supported by funding from Novartis Pharmaceuticals.